Compression socks reduce running-induced intestinal damage - Zadow, E. K.; Edwards, K. H.; Kitic, C. M.; Fell, J. W.; Adams, M. J.; Singh, I.; Kundur, A.; Johnston, A. N. B.; Crilly, J.; Bulmer, A. C.; Halson, S. L.; Wu, S. S. (The Journal of Strength and Conditioning Research, 2022)
Exercise is associated with a reduction in splanchnic blood flow that leads to the disruption of intestinal epithelium integrity, contributing to exercise-induced gastrointestinal syndrome. Strategies that promote intestinal blood flow during exercise may reduce intestinal damage, which may be advantageous for subsequent recovery and performance. This study aimed to explore if exercise-associated intestinal damage was influenced by wearing compression garments, which may improve central blood flow. Subjects were randomly allocated to wear compression socks (n = 23) or no compression socks (control, n = 23) during a marathon race. Blood samples were collected 24 hours before and immediately after marathon and analyzed for intestinal fatty acid-binding protein (I-FABP) concentration as a marker of intestinal damage. The magnitude of increase in postmarathon plasma I-FABP concentration was significantly greater in control group (107%; 95% confidence interval [CI], 72-428%) when compared with runners wearing compression socks (38%; 95% CI, 20-120%; p = 0.046; d = 0.59). Wearing compression socks during a marathon run reduced exercise-associated intestinal damage. Compression socks may prove an effective strategy to minimize the intestinal damage component of exercise-induced gastrointestinal syndrome.